Post-weaning exposure to bisphenol A induces histological changes in the liver - Mohamad Zaid, Siti Sarah; Rohim, Siti Nur Hajar; Goh, Yong Meng; Mohamed Mustapha, Noordin (Universiti Putra Malaysia Press, 2019)
Bisphenol A (BPA) is an endocrine disrupting chemical (EDC) widely used in industry as a plasticizer for the production of polycarbonate plastics and epoxy resins. The liver is highly sensitive to BPA, even at low doses. The objective of the study is to investigate the effect of BPA on histo-architecture of the liver in post-weaning rats. Post-weaning female rats were exposed to BPA by oral gavage over a six weeks period. The results showed that even at low environmental doses, BPA exposure had adverse effects on the liver histo-architecture, thereby disrupting the functions of cellular. The administration of BPA resulted in severe hepatocytes necrosis, dilated sinusoid, and depicting features of conspicuous Kupffer cells. The results may be due to the generation of reactive oxygen species (ROS) by BPA. In conclusion, post-weaning exposure of BPA resulted in significant histological alterations due to ROS generation.